Excision recommended in high‐risk patients: Revisiting the diagnosis of papilloma on core biopsy in the context of patient risk. Issue 2 (30th January 2019) - Chen, Yun An; Mack, Julie A.; Karamchandani, Dipti M.; Zaleski, Michael P.; Xu, Liyan; Dodge, Daleela G.; Chetlen, Alison L.
Abstract: We investigate the clinical history, past medical history, and risk status in women with benign intraductal papillomas(IDP). We observed an upgrade rate of 3.9% to ductal carcinoma in situ (DCIS) and upgrade rate of 10.7% to a high‐risk lesion. Prior or concurrent atypia or cancer and high‐risk status had a significant increase risk of upgrade. Surgical excision of papillomas is recommended especially in high‐risk patients and women with concurrent or history of atypia or malignancy.